A review of conventional and new-generation aircraft starter/generators in perspective of electric drive applications - Oksuztepe, Eyyup; Kaya, Ufuk; Kurum, Hasan (Emerald Group Publishing Ltd, 2023)
Purpose More electric aircraft (MEA) is defined as the extensive usage of electric power in aircraft. The demand for electric power in new generation aircraft rises due to environmental and economic considerations. Hence, efficient and reliable starter/generators (SGs) are trending nowadays. The conventional main engine starting system and power generation system can be replaced with an individual SG. The constraints of the SG should be investigated to handle the aviation requirements. Even though the SG is basically an electric machine, it requires a multidisciplinary study consisting of electromagnetic, thermal and mechanical works to cope with aviation demands. This study aims to review conventional and new-generation aircraft SGs from the perspective of electric drive applications. Design/methodology/approach First of all, the importance of the MEA concept has been briefly explained. Also, the historical development and the need for higher electrical power in aircraft have been indicated quantitatively. Considering aviation requirements, the candidate electrical machines for aircraft SG have been determined by the method of scoring. Those machines are compared over 14 criteria, and the most predominant of them are specified as efficiency, power density, rotor thermal tolerance, high-speed capability and machine complexity. The features of the most suitable electrical machine are pointed out with data gathered from empirical studies. Finally, the trending technologies related to efficient SG design have been explained with numeric datasets. Findings The induction motor, switched reluctance motor and permanent magnet synchronous motor (PMSM) are selected as the candidate machines for SGs. It has been seen that the PMSM is the most preferable machine type due to its efficient operation in a wide range of constant power and speed. It is computationally proven that the using amorphous magnetic alloys in SG cores increases the machine efficiency more. Also, the benefits of high voltage direct current (HVDC) use in aircraft have been explained by a comparison of different aircraft power generation standards. It is concluded that the HVDC use in aircraft decreases total cable weight and increases aircraft operation efficiency. The thermal and mechanical tolerance of the SG is also vital. It has been stated that the liquid cooling techniques are suitable for SGs. Originality/value The demand for electrical power in new generation aircraft is increasing. The SG can be used effectively and efficiently instead of conventional systems. To define requirements, constraints and suggestions, this study investigates the SGs from the perspective of electric drive applications.
Keywords: Aircraft; Starter; generator; More electric aircraft; Electric drives